2019
DOI: 10.3390/medicina55030079
|View full text |Cite
|
Sign up to set email alerts
|

How to Manage Impacted Third Molars: Germectomy or Delayed Removal? A Systematic Literature Review

Abstract: Objectives: The aim of this systematic review is to evaluate and compare the risks and benefits of germectomy and delayed removal of third molars and develop a patient management algorithm for second molar eruption in syndrome/incompliant patients. Materials and Methods: A literature search was performed in the following databases; the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed, Scopus, and Web of Science. Last search was done on July 2nd, 2018 including articles published from the last 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 39 publications
0
26
0
5
Order By: Relevance
“…Since it has been reported that in the daily clinical practice many dentists used to prescribe several days of antibiotics even after oral surgery and even without appropriate posology, it has to be pointed out that this malpractice is probably caused by the scarce knowledge of the WHO guidelines and of the pharmacological properties of the molecules [37]. Autonomy in interpreting the drug manufacturer's recommendations may even be related to the operator's personal clinical experience in treating a particular disease [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Since it has been reported that in the daily clinical practice many dentists used to prescribe several days of antibiotics even after oral surgery and even without appropriate posology, it has to be pointed out that this malpractice is probably caused by the scarce knowledge of the WHO guidelines and of the pharmacological properties of the molecules [37]. Autonomy in interpreting the drug manufacturer's recommendations may even be related to the operator's personal clinical experience in treating a particular disease [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…V.13, N. 47 p. 823-835, Outubro/2019 -ISSN 1981-1179 Edição eletrônica em http://idonline.emnuvens.com.br/id mandíbula e comunicação oroantral. A remoção precoce de terceiros molares anormais pode reduzir o risco aumentado de complicações (STADERINI et al, 2019;YU et al, 2017).…”
Section: Revisão Da Literaturaunclassified
“…Na ausência de sintomas subjetivos, pelo menos três fatores radiográficos geralmente determinam a decisão de remover um terceiro molar mandibular impactado/semi-impactado: reabsorção na superfície distal do segundo molar, perda óssea marginal na superfície da raiz distal do segundo molar e um aumento do espaço periodontal ou cisto ao redor da coroa do terceiro molar (EA; L, 2018). Assim, se pelo menos uma dessas patologias estiver presente na radiografia, o terceiro molar deve ser removido (STADERINI et al, 2019).…”
Section: Introductionunclassified
“…So the restoration should be functionally optimal to bear high stress concentration (eg, patients with seizures). [ 1 ] Teeth with large defects are usually repaired by post-core-crown after root canal treatment. [ 2 ] The use of fiber or cast post requires the preparation of the root canal, which may reduce the flexural resistance of the remaining teeth.…”
Section: Introductionmentioning
confidence: 99%